An exploratory study on machine learning frameworks - Flexa, Caio; Gomes, Walisson; Viademonte, Sergio (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2019: Anais do XVIII Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2019.6476, 2019)
This document describes a preliminary study on computing frameworks and technologies, for the purpose of developing machine learning (ML) system applications. Several frameworks, application programming interfaces and programming libraries for ML algorithms have been developed in the last few years, in a relatively short period of time, making difficult a decision on which one to chose in a particular application. This study reviews some criteria and performs a preliminary evaluation of some of the most used ML technologies for developing system applications, with the purpose to guide and facilitate the decision on which of them to apply, given a particular application.